Proceedings of the 2017 International Conference on Digital Health 2017
DOI: 10.1145/3079452.3079496
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Soft Data for Mass Provision of Stereoacuity Testing Through a Serious Game for Health

Abstract: Mass provision of healthcare through a digital medium can be greatly enhanced by the use of serious games. The accessibility and engagement provided by a serious game to the subject can significantly increase participation. The commercial games industry employs numerous techniques to analyse soft data collected from early users of an application to evolve the application itself and improve the experience of playing it. A game for mass stereoacuity testing of young children is used as a case study in this paper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…The front camera is used to monitor the viewing distance and correct the stimulus for changes in viewing distance, meaning that patients are free to hold the device how they wish rather than requiring clinician intervention to maintain the correct distance. Most importantly, the stereotest task is embedded in a fun game that uses colors, sounds, and animation to keep children engaged and responsive 18. We believe that this combination of features offers unique advantages, which are not achieved either by current clinical stereotests or the research tests described in the previous paragraphs.…”
Section: Introductionmentioning
confidence: 99%
“…The front camera is used to monitor the viewing distance and correct the stimulus for changes in viewing distance, meaning that patients are free to hold the device how they wish rather than requiring clinician intervention to maintain the correct distance. Most importantly, the stereotest task is embedded in a fun game that uses colors, sounds, and animation to keep children engaged and responsive 18. We believe that this combination of features offers unique advantages, which are not achieved either by current clinical stereotests or the research tests described in the previous paragraphs.…”
Section: Introductionmentioning
confidence: 99%
“…We found that Staircase algorithm is often used in the literature, with some minimal differences. In papers [17,10,16,15], stereoacuity is measured using staircase, the disparity is increased/decreased of one level. The disparity is increased of one level and decreased of two levels in paper [6].…”
Section: Related Workmentioning
confidence: 99%
“…Also, Ushaw et al proved the help given by serious games for health. Their game for measuring the stereoacuity of young children has been tested by an initial user group and was proven successful, although a testing protocol and rapid analysis of the data is needed [22]. In this paper, our main research objective is immersive VR and serious games in healthcare, more specifically in the rapid assessment and treatment of acute stroke, are relatively common emergency neurological disease.…”
Section: Serious Games In Healthcarementioning
confidence: 99%